Identification of chemical constituents of agarwood (aquilaria malaccencis) oil extracted by supercritical fluid and hydrodistillation method - Siti Noor Fahimah, Jusoh (2014)
Agarwood oil is regarded as the one of the most valuable essential oil due to its odours and applications in the perfumery industry. The essential oil was extracted by different extraction methods: i.e; hydrodistillation (HD) and supercritical fluid extraction (SFE), and analysed via gas chromatography flame-ionization detector (GC-FID) and gas chromatography mass spectrometer (GC-MS). This research aims to identify the optimum extraction condition for isolating agarwood essential oil and to profile chemical constituents via SFE. The effects of different parameters such as pressure, temperature, volume of modifier and static time were investigated. The optimum parameter; pressure of 41.37 MPa, temperature of 60 °C, 48 mL of modifier and 30 minutes of static time. The recovery of essential oils were as follows; 0.20 % for HD, 0.65 % for SFE without modifier and 1.73 % with modifier. Fourty three compounds were identified in the hydrodistilled oil with agarospirol (13.57 %), tetradecanal (6.63 %) and pentadecanal (4.9 %) as major compounds. However for SFE, it composed by fourty seven compounds with eudesmol (13.68 %), oxo-agarospirol (4.54 %) and 2hydroxyquaia-1(10),11,15-oic acid (3.24 %) for non-modifier meanwhile with modifier ; eudesmol (11.53-13.75 %), hexadecanol (4.58-5.00 %) and dehydrojinkoh-eremol (2.42 -2.91 %). Data shows that SFE with 41.37 MPa, 60 °C and 48 mL ethanol, gives higher recovery meanwhile nonmodified SFE and conventional extraction yields were comparable.